Differentiated instruction to develop Al-Azhar students' writing fluency - Abdelkareem Ali Abdelnaeim Mehany (Northern Negros State College of Science and Technology (NONESCOST), 2022)
Writing in English with confidence is a matter of great concern for non-native speakers. Since writing fluently requires a multi-dimensional mastery of language skills, students always regard it as an open question. This paper investigates writing skills which seem to be the least favored and most problematic skills to acquire in foreign language acquisition. The purpose of the study was to investigate the impact of Differentiated Instruction (DI) on the English writing fluency of the students in the first year of secondary education in Al-Azhar Institutes. To answer the study questions, the researcher adopted the quasi-experimental approach using the one-group design. The study subjects were thirty two (32) students who had been randomly chosen from the Secondary education of Al-Azhar Institutes in Sohag governorate, Egypt. The sampling method is probability sampling which means that every individual in the population has a chance of being selected. The researcher used a program based on Differentiated Instruction's theory in teaching the study group in the second term of the year (2018-2019). The program consisted of 12 units. Each unit has four lessons. To measure the effect of the program, the researcher designed and validated a writing fluency test to be used as a pre and post-test. The data of the study were analyzed, using SPSS 19 software, to confirm the test reliability. The researcher used a t-test to spot the statistical differences in students' performance before and after the intervention of the program. The study indicated that there are statistically significant differences at the level of (0.05) in English writing fluency skills of the first-year students in favor of the post-test. This meant that the use of the program had a significant impact on developing the students' writing fluency at Al-Azhar Institutes. Based on those findings, the study recommended implementing the suggested program to bring about better outcomes in students' writing fluency. It also was suggested that further research should be conducted concerning other language domains such as reading and listening.